The Problem of Land Erosion and Landslips in the Hoshiarpur Siwaliks - Puri, G. S. (Indian Forester, 1949)
From the above discussion it follows that the Hoshiarpur Siwalik hills, on account of their structure, composition of the rock and the inherent geological activity in Northern India, are predisposed to erosion and landslips on their southern dip slopes. So a certain amount of erosion normally occurs in these hills. Erosional gullies are formed by the action of rain which percolates in the sub-soil and seeps through the strata issuing on the dip slope with a force depending upon the density of vegetation. A dense vegetation on thc scarp slopes and at higher elevations on thc dip slope provides a protective cover against the physical and physiological action of rain in accelerating the normal geological erosion. Evidence is re-stated to show that the present state of erossion in the Hoshiarpur Siwaliks was the result of irrational and nonecological uses (rather misuses) of vegetation, dating back to the last one or two centuries. While no amount of emphasis is necessary on the value of afforestration to check the erosion it is suggested that (1) a planned and determined programme of planting on scarp slopes and higher elevations on the dip slopes with suitable specics be launched without delay; (2) the methods of forest exploitation in other areas in the Siwaliks be carefully examined in the light of ecological data presented in these pages; (3) extensive and intensive ecological studies of forests be made in the Siwaliks in special regards to soil conservation and spots susceptible to erosion be forthwith tackled by special afforestation parties. The suggestions made here may be viewed in relation to a paper submitted by me to the Ministry of Agriculture in June 1947. The need for an organized and intensive ecological research is most urgent for tackling the problem of soil erosion in India now more than it was ten years ago.